Stochastic component to development of class I major histocompatibility complex-specific T cells. - Itano, A (1994)
The mechanism by which an initially uncommitted cell chooses between alternative fates is a central issue in developmental biology. In the mammalian thymus, CD4 helper T cells and CD8 cytotoxic T cells arise from a common precursor that expresses both CD4 and CD8. The choice between the CD4 and CD8 lineage is linked to the specificity of the T-cell antigen receptor expressed by a thymocyte, but whether lineage commitment is stochastic or instructed has not been definitively resolved. We present evidence that expression of a constitutive CD8 transgene during thymic selection permits development of mature CD4 cells bearing the class I-restricted F5 T-cell antigen receptor. These results suggest that there is a stochastic component to the development of class I major histocompatibility complex-restricted T cells.